(untitled) (Economic studies journal, 2024)
The study aimed to identify the elements of the promotional mix used by Al-Aseel Company and directed to consumers of its products in the city of Benghazi, as well as to identify the extent to which the elements of the promotional mix influence the purchasing behavior of consumers. To achieve this goal, the descriptive approach was followed, and the questionnaire tool was used to collect primary data from the study sample, which The number of them reached (217) consumers who were randomly selected. After analyzing the field data, the study reached many results, the most important of which are; Al-Aseel Company uses all elements of the promotional mix in general in promoting its products, in order to influence consumer behavior, and that the sales activation element is the element most used by Al-Aseel Company in promoting its products from the point of view of consumers, and the public relations element is the least used element. By the company, and that there is a statistically significant effect of the promotional mix in its dimensions (advertising dimension, personal selling, sales activation, and public relations dimension) on the behavior of consumers of Al-Aseel Company’s products residing in the city of Benghazi.